2020
DOI: 10.1016/j.carbon.2020.01.114
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity reduction in carbon nanotube by fullerene encapsulation: A molecular dynamics study

Abstract: Single-walled carbon nanotubes (SWCNTs) in their pristine form have high thermal conductivity whose further improvement has attracted a lot of interest. Some theoretical studies have suggested that the thermal conductivity of a (10, 10) SWCNT is dramatically enhanced by C 60 fullerene encapsulation. However, recent experiments on SWCNT bundles show that fullerene encapsulation leads to a reduction rather than an increase in thermal conductivity. Here, we employ three different molecular dynamics methods to stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Our findings corroborate predictions that water filling should decrease a nanotube’s thermal conductivity by increasing the scattering rate of long-wavelength acoustic phonons . With qualitatively similar trends reported for filling of CNTs with fullerenes , and ionic liquids, the combined experimental evidence points toward this phenomenon being, to at least some extent, independent of the confined molecular species. Furthermore, with a similar effect recently observed in a metal-organic framework, fluids may well act to impede thermal conductivity in a broad range of solid-state nanopores.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings corroborate predictions that water filling should decrease a nanotube’s thermal conductivity by increasing the scattering rate of long-wavelength acoustic phonons . With qualitatively similar trends reported for filling of CNTs with fullerenes , and ionic liquids, the combined experimental evidence points toward this phenomenon being, to at least some extent, independent of the confined molecular species. Furthermore, with a similar effect recently observed in a metal-organic framework, fluids may well act to impede thermal conductivity in a broad range of solid-state nanopores.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, early experimental work reported an enhancement of κ upon fullerene encapsulation in a single-walled CNT (SWCNT) buckypaper, in agreement with a number of subsequent theoretical studies. A recent experiment, however, demonstrated the opposite effect in fullerene-filled CNT bundles: a reduction of κ with respect to unfilled tubes is observed . This sparked a revision of previous theoretical work, with more recent molecular dynamics simulations pointing to fullerenes’ capability of impeding heat transfer in the CNT through enhanced phonon scattering. , The thermal impedance confined molecular species add in series to the one of an unfilled CNT may therefore be more important than the one they add in parallel to it (scenario 2 in Figure a). Water filling has been suggested to similarly reduce the thermal conductivity of CNTs, but experimental verification remains challenging.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…It has also been used to study the particular thermal transport properties of specific materials, in-cluding various two-dimensional (2D) materials, 64,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] vdW structures based on 2D materials, [104][105][106][107][108][109][110] and quasi-one-dimensional materials. [111][112][113] There are applications focused on revealing unique phonon transport mechanisms. [114][115][116][117][118][119][120] The high efficiency of gpumd also enabled high-throughput thermal transport simulations that were used as training/testing data for machine learning models of interfacial thermal transport.…”
Section: Overview Of the Gpumd Packagementioning
confidence: 99%
“…Their interpretation does not seem, however, conclusive, since the classical MD simulations carried out to support their claim did show a sizable deformation of the CNT walls only after an artificial increase of the strength of the fullerene–CNT van der Waals interaction, although the fact that CNT bundles were investigated increases the complexity of the problem and the interpretation in terms of single peapods features. Subsequent computational studies , showed that C 60 molecules are able to induce additional phonon scattering, thus reducing the phonon mean free path and the thermal conductance. The effect is most prominent in the low-frequency region, where ref found that the group velocities of the acoustic branches of a CNT­(9,9) peapod were considerably reduced when compared with pristine CNT, while the effect was nearly absent for CNT­(10,10) peapods.…”
Section: Introductionmentioning
confidence: 99%